2015
DOI: 10.1007/s12223-015-0390-2
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related blood stream infection caused by Raoultella ornithinolytica

Abstract: Raoultella spp. representatives are Gram-negative capsulated, nonmotile rods. These bacteria are found in the natural environment: plants, water, soil and insects. R. ornithinolytica is one of the three species of Raoultella. R. ornithinolytica is the only species within the genus which has the ability to produce ornithine decarboxylase. Human infections related to R. ornithinolytica are exceedingly rare. The present case report describes catheter-related blood stream infection caused by R. ornithinolytica and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 11 publications
0
35
1
Order By: Relevance
“…As well as the well-known clinical presentations of R. ornithinolytica infections, such as primary or cholangitis bloodstream infection, [3][4][5]7,14,16,18,20,22 catheter-related bloodstream infection, 8,26 biliary tract infection, 3-5 urinary tract infection, 5,15,21 and skin infection, 19,20 cases of respiratory infection including community-and hospital-acquired pneumonia and pleural effusion were also identified in this study, and these have been poorly reported. Boattini et al recently reported three cases of community-acquired pneumonia and three cases of hospital-acquired pneumonia among 25 cases of R. ornithinolytica infection over a 5-year period in six university hospital centres in Lisbon.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…As well as the well-known clinical presentations of R. ornithinolytica infections, such as primary or cholangitis bloodstream infection, [3][4][5]7,14,16,18,20,22 catheter-related bloodstream infection, 8,26 biliary tract infection, 3-5 urinary tract infection, 5,15,21 and skin infection, 19,20 cases of respiratory infection including community-and hospital-acquired pneumonia and pleural effusion were also identified in this study, and these have been poorly reported. Boattini et al recently reported three cases of community-acquired pneumonia and three cases of hospital-acquired pneumonia among 25 cases of R. ornithinolytica infection over a 5-year period in six university hospital centres in Lisbon.…”
Section: Discussionmentioning
confidence: 88%
“…A literature search identified 86 reported cases of R. ornithinolytica (formerly Klebsiella ornithinolytica), [3][4][5][6][7][8][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and half of these cases were reported in 2015. 10,12,[24][25][26] A high rate of hospital-acquired infection was observed in the present study (49%), which may be explained by the high proportion of patients who had undergone invasive procedures (48%) involving, for example, urinary catheters, mechanical ventilation, and port catheters. Physicians should take into consideration the fact that cases of R. ornithinolytica infection acquired in hospital are poorly reported in the literature and should adapt their management of infection control and prevention accordingly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RO is a rare human infection and only small number of patients have been reported postoperatively. Fewer cases are reported that relate to pulmonary challenged patients [1]. It is observed that the effects of RO are greater and more frequent in immunosuppressed and especially in oncological patients.…”
Section: Introductionmentioning
confidence: 99%